Accuracy of Screening Methods for the Diagnosis of Breast Disease - Furnival, Isobel G. (1970)
Clinical examination, thermography, and 70-mm. mammography were performed in 891 patients—414 presented to hospital with symptoms of breast disease and 477 were asymptomatic. Comparison of the diagnostic accuracy of these methods showed that neither thermography nor 70-mm. mammography has a useful place as an isolated screening procedure for breast cancer. In fact, we consider such a policy dangerous.